2019
DOI: 10.1111/dme.13874
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA mutation m.3243A>G is associated with altered mitochondrial function in peripheral blood mononuclear cells, with heteroplasmy levels and with clinical phenotypes

Abstract: Aims To investigate the associations among heteroplasmy levels (i.e. the proportions of mutant and wild-type mitochondrial DNA in the same cell), mitochondrial function and clinical severity of the m.3243A>G mutation.Methods A total of 17 participants carrying the m.3243A>G mutation and 17 sex-and age-matched healthy controls were included in this study. Heteroplasmy levels of the m.3243A>G mutation in leukocytes, saliva and urine sediment were determined by pyrosequencing. The clinical evaluation included end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
2
14
1
Order By: Relevance
“…Our results provided supports to the emerging role of m.3243A > G in bone mineralization deficiency. We and another group recently reported that m.3243A > G mutation was associated with loss of bone density in affected patients [11,12]. In the current study, we further confirmed this newly characterized pathological phenotype (Table 1), and started to unveil the underlying signaling pathways linking the m.3243A > G mutation to the loss of bone density.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results provided supports to the emerging role of m.3243A > G in bone mineralization deficiency. We and another group recently reported that m.3243A > G mutation was associated with loss of bone density in affected patients [11,12]. In the current study, we further confirmed this newly characterized pathological phenotype (Table 1), and started to unveil the underlying signaling pathways linking the m.3243A > G mutation to the loss of bone density.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, a previous case-control study indicated that the m.3243A > G mutation is associated with premature bone aging, characterized by reduced bone mass, impaired structure and strength [11]. Our recent study further suggested that high levels of the m.3243A > G mutation in blood leukocytes were significantly associated with lower bone mineral density [12].…”
Section: Introductionmentioning
confidence: 50%
“…Mitochondrial function evaluation was performed as previously described [19]. A total of 4 ml venous blood samples from each individual in F1957 were collected into vacuum tubes containing EDTA.…”
Section: Methodsmentioning
confidence: 99%
“…The other manifestations of m.3243A>G in MIDD contained the following, namely central neurological and psychiatric features, ophthalmic disease, myopathy, cardiac disorders, renal disease. endocrine disease, gastrointestinal disease, and miscellaneous features [9].…”
Section: Case Reportmentioning
confidence: 99%